2020
DOI: 10.1134/s0020168520020120
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Fe3O4 Films Grown on R-Plane Sapphire by Pulsed Laser Deposition

Abstract: We have studied the influence of growth temperature and molecular oxygen pressure on the properties of thin (≤180 nm) epitaxial magnetite (Fe 3 O 4 ) (001) films grown by pulsed laser deposition on R-plane single-crystal sapphire (Al 2 O 3 ( 012)) with and without MgO seed layer. The electrical, morphological, and structural characteristics of the films have been investigated as functions of growth conditions. Fe 3 O 4 has been shown to have a stable growth plateau at pressures in the range (4-9) × 10 -5 Torr.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The tilt can be important; for example, the (100) MgO may epitaxially grow on (102) Al 2 O 3 with a tilt up to 5° or 6°, depending upon the growth temperature . From such results, it was concluded that the surface state of r-plane sapphire is an important factor leading to the tilted growth of the epilayer. In our present case, it is not surprising that the epitaxial growth of ZFO on the r-plane Al 2 O 3 occurs at RT with a tilt of about 4.7°.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The tilt can be important; for example, the (100) MgO may epitaxially grow on (102) Al 2 O 3 with a tilt up to 5° or 6°, depending upon the growth temperature . From such results, it was concluded that the surface state of r-plane sapphire is an important factor leading to the tilted growth of the epilayer. In our present case, it is not surprising that the epitaxial growth of ZFO on the r-plane Al 2 O 3 occurs at RT with a tilt of about 4.7°.…”
Section: Resultssupporting
confidence: 52%
“…It must be noticed that in the case of the epitaxial growth of various oxide films on the r-cut sapphire substrate, the surface plane of the oxide film was tilted with respect to the (102) plane of sapphire. This phenomenon was observed for instance in the epitaxial growth of ZnO, CeO 2 , MgO, , or Fe 3 O 4 . The tilt can be important; for example, the (100) MgO may epitaxially grow on (102) Al 2 O 3 with a tilt up to 5° or 6°, depending upon the growth temperature .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation